The use of interventional ultrasound in early pregnancy complications. Issue 1 (February 2013) - Reid, Shannon; Casikar, Ishwari; Condous, George
Abstract: Background : The use of ultrasound to establish pregnancy location, viability and gestational age in the first trimester is well established. In addition to the conventional uses of ultrasound in early pregnancy, interventional ultrasound may also be used to guide clinicians during surgical procedures for the management of early pregnancy complications (i.e. treatment of ectopic pregnancy, caesarean section scar pregnancy, molar pregnancy, retained products of conception, and removal of intra‐uterine devices in early pregnancy). Aims : This review discusses the role of interventional ultrasound as it pertains to the management of first trimester complications, particularly with regard to the use of ultrasound in conjunction with surgical modalities. Materials and Methods : This review was based on recently published research, as cited in the PubMed database, regarding the use of either transvaginal or transabdominal ultrasound to assist with the management of early pregnancy complications. Conclusions : In addition to the diagnostic capabilities of ultrasound in early pregnancy, interventional ultrasound plays an important role in the management of various first trimester pregnancy complications. With the advent of more conservative approaches to early pregnancy complications, interventional ultrasound is a viable option which is not only safe in experienced hands but also enables fertility preservation.